Pengaruh Konsumsi Telur Ayam Ras Rebus Terhadap Peningkatan Kadar HB Pada Ibu Hamil Trimester II Di BPM Wilayah Kerja Puskesmas Klaten Tengah - Sugita Sugita; Supiati Supiati (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Effect, Boiled Eggs, Pregnancy, Hemoglobin. The purpose of this study was to prove that Effect, Boiled Eggs, Pregnancy, Hemoglobin. To determine the effect of boiled eggs consumption to the increase of hemoglobin levels in the second trimester of pregnancy in Puskesmas Klaten Tengah. This study used a quasi-experimental research design with a non-randomized control group pretest-posttest design. The population in this study were pregnant women in Puskesmas Klaten Tengah with 30 samples. Sampling using purposive sampling with 15 samples as the treatment group and 15 samples as a control group. Analysis of the data by independent sample t-test. The hemoglobin levels change of the second trimester pregnant women between the pre and post boiled eggs consumption group and Fe tablet consumption group and non consumption showed 0.001 (<0.05) of p-value, it means that there have a differences in hemoglobin levels between the pre and post boiled eggs consumption group and Fe tablet consumption group and non consumption. Boiled eggs consumption are effective to increase hemoglobin levels in the second trimester of pregnancy in Puskesmas Klaten Tengah.